The European Parliament as a developing legislature: coming of age in trilogues?. Issue 5 (14th May 2017) - Roederer-Rynning, Christilla; Greenwood, Justin
ABSTRACT: This article examines the institutionalization of the European Parliament-as-a-legislature. It draws on the political development scholarship to conceptualize institutionalization and highlight the role of the environment in the development and decay of political institutions. On this premise, we argue that the political significance of the European Parliament (EP) depends on its capacity to develop strong institutions enabling it to 'exist apart' from its environment. We identify the embrace of codecision as a critical moment of the institutionalization of the EP-as-a-legislature and explore the value of the political development perspective in a comparative-historical study of trilogues in the EP. We present a typology of institutionalization of trilogues and argue that a model of generic parliamentary approach to trilogues is taking roots. While substantiating the thesis of the EP as a potentially autonomous institution, our findings also call for research into the resilience and sources of institutional patterns of trilogues.